JAEPL, Vol. 5, Winter 1999-2000 (Journal of the Assembly for Expanded Perspectives on Learning, 1999)
Essays David Bleich. Learning from Everyone. In the teaching of writing and literature, it would be helpful to teachers and students to encourage students to overtake, use, and reuse one another's various uses of language in essays and other course work. Lisa Tyler. Narratives of Pain: Trauma and the Healing Power of Writing. Writing about traumatic events is useful, healing, and meaningful, and such work deserves a place in the composition classroom. Bradford A. Barry. Writer Motivation: Beyond the Intrinsic/Extrinisic Dichotomy. This article articulates and develops a much needed theory of communication motivation which shows how we can nurture in our students rhetorically-based intrinsic motivations. Kia Jane Richmond. The Ethics of Empathy: Making Connections in the Writing Classroom. Instead of relying on our memories, we should listen empathetically to our students so that we can help them with their writing as individuals—and not as carbon copies of ourselves. Catherine L. Hobbs. The Architectonics of Information: Ancient Topical Thought and Postmodern Information. This paper examines the usefulness of thought patterns from ancient rhetoric as they have been appropriated historically and as potentially applicable concepts for the present and future in today's interlinked electronic environment. Susan A. Schiller. Spirituality in Pedagogy: 'A Field of Possibilities.' Students' responses to a spiritual approach to teaching provide evidence of the efficacy inherent in such an approach. Reviews Anne E. Mullin. Teaching Writing Creatively. (David Starkey, Ed., 1998). Keith Rhodes. Zen in the Art of Rhetoric: An Inquiry into Coherence. (Mark Lawrence McPhail, 1996). Ellen Davis. Women in Praise of the Sacred: 43 Centuries of Spiritual Poetry by Women. (Jane Hirshfield, Ed., 1994). Jean R. Trounstine. Educational Drama and Language Arts: What Research Shows. (Betty Jane Wagner, 1998).